The Independence of Peru in two traditions of Ricardo Palma - Chiri Jaime, Sandro (2023)
his essay analyzes the civic spirit which Ricardo Palma used to write a set of traditions during the process of Peruvian Independence and, while doing so, he privileges the unitary spirit of the nation over the political conflicts of those times. Likewise, the text analyzes two stories, “Con días y ollas venceremos” and “La tradición del Himno Nacional”, with the purpose of valuing, in the first one, the risks that Peruvians of diverse origins assumed to conquer the so longed emancipation from the colonial administration; and, in the second one, to recognize the merit of the lyrics and music of the National Anthem of Peru, as well as its intangibility, as it was the work of the Peruvians who founded the Republic. Keywords: José de San Martín, Simón Bolívar, Francisco Luna Pizarro, José Bernardo Alcedo, José de la Torre Ugarte, independence, emancipation, Republic, patriots, militarism, music.